Micro and Small Enterprises' Export Competencies and Cooperation in Indonesia - Tambunan, Tulus Tahi Hamonangan (Journal of Developing Economies, 2024)
Micro, small, and medium enterprises (MSMEs) have an important role in Indonesia to play not only as a source of employment but also growth of gross domestic product (GDP) and exports, specially manufactured goods such as garments, food, footwear, electronics, and crafts. To support MSME exports, the Indonesian government hopes to build stronger collaboration with them. Many journal articles regarding exports of MSMEs have been executed in developing countries. However, no research has been conducted concerning the cooperative role of MSMEs in supporting their exports. Therefore, this descriptive study filled the gap by analyzing the cooperation of MSMEs in supporting their exports in Indonesia by analyzing secondary data from the 2019 Profile of Micro and Small Industries (MSIs) in the Manufacturing Industry from the Indonesian Statistics (BPS) and online database from the Indonesian Minister of Cooperative and Small and Medium Enterprise. Although the data does not provide further information regarding how many MSEs are members of cooperatives who export, the scatter plot in this study shows that there is a positive relationship between the number of MSEs who export and the number of MSEs who are members of cooperatives. Even though other factors had a stronger influence on export competencies, cooperatives still supported MSEs to export their goods. This study contributes to more substantial empirical evidence on the relationship between cooperatives and MSMEs in Indonesia and developing countries.